Cross-Gendered Literary Voices
X, 243 p.
Keywords: This book investigates male writers' use of female voices and female writers' use of male voices in literature and theatre from the 1850s to the present, examining where, how and why such gendered crossings occur and what connections may be found between these crossings and specific psychological, social, historical and political contexts.